Single atom transistor in a 1D optical lattice - Micheli, A; Daley, A; Jaksch, D; Zoller, P (American Physical Society, 2004)
We propose a scheme utilizing a quantum interference phenomenon to switch the transport of atoms in a 1D optical lattice through a site containing an inpurity atom. The impurity represents a qubit which in one spin state is transparent to the probe atoms, but in the other acts as a single atom mirror. This allows a singe-shot quantum nondemolition measurement of the qubit spin.